Enzymatic syntheses, characterizations and applications of fatty hydroxamic acid derivatives from canola and palm oils - Jahangirian, Hossein (2012)
Fatty hydroxamic acids and derivatives have attracted many researches due to their pharmaceutical and analytical applications. They have been widely applied as food additives, growth factors, antibacterial agents, fungicides, tumor inhibitors, enzyme inhibitors and metal chelators. A common method for the preparation of hydroxamic acids and their derivatives is via reaction of hydroxylamine or their derivatives with alkyl esters or activated carboxylic acids. However these reactions often contain many steps and require expensive chemicals. In this study, four types of N-substituted fatty hydroxamic acids as the following were synthesized. Phenyl fatty hydroxamic acids (PFHAs), synthesized by reaction of canola oil, palm kernel oil or palm stearin with N-phenyl hydroxylamine (N-PHA). Methyl fatty hydroxamic acids (MFHAs), synthesized by reaction of palm kernel oil and Nmethyl hydroxylamine (N-MHA). Isopropyl fatty hydroxamic acids (IPFHAs), synthesized by reaction of palm kernel oil and N- isopropyl hydroxylamine (NIPHA). Benzyl fatty hydroxamic acids (BFHAs), synthesized by reaction of palm kernel oil and N-benzyl hydroxylamine (N-BHA). The reactions were carried out in a sealed flask, incubated in water bath shaker at 39°C for 72 hours and catalyzed by immobilized lipase (Lipozyme TL IM or RM IM). The products were then separated by filtration, solvent extraction followed by evaporation of the solvent. The products were characterized by The FT-IR and 1H NMR spectroscopies, CHN elemental analysis and qualitative color test with Cu(II), Fe(III) and V(V) ions. The products as chelating agents were used for extraction of Cu(II) or Fe(III) ions from samples containing mixture of metal ions in aqueous solution. The products and their copper complexes were also evaluated for antibacterial activity on Escherichia coli (E. Coli) and Staphylococcus aureus (S. Aureus) and antifungal activity on Candida parapsilosis (C. parapsilosis), Candida albicans (C. albicans) and Aspergillus fumigatus (A. fumigatus) using disk and well diffusion methods. The conversion percentage of phenyl hydroxylaminolysis of the two different commercial canola oils (Ladan and Krystal brands), palm stearin oil and palm kernel oil were 55.6, 52.2, 51.4 and 49.7 %, respectively. In addition the conversion percentage of methyl hydroxylaminolysis, isopropyl hydroxylaminolysis and benzyl hydroxylaminolysis of the commercial palm kernel oil were 77.8, 65.4 and 61.7 %, respectively. The FTIR and 1H NMR spectroscopic data, CHN elemental analysis and qualitative color test on the purified products confirmed the existence of PFHAs, MFHAs, IPFHAs and BFHAs.